Problems Behind Fostering Autonomous Learning During Learner-Centered Instruction Paradigm in EFL Class - Absharini Kardena (Institut Agama Islam Negeri Madura, 2022)
Promoting students to be independent learners is challenging for English teachers. Students accustomed to learning based on the teacher's instruction and usually waiting for any materials will find learning through autonomous learning difficult. Moreover, English teachers would also obligate to lead the students to foster their learning independently. This article aims to analyze any difficulties found in EFL classes during fostering students' autonomous learning. The research was conducted under a qualitative approach by using a phenomenology design. The research was conducted at MAN Kota Solok and further developed by involving 4 English teachers and 160 students in four classes. The research found that the problems in fostering autonomous learning in EFL classes lie in 4 reasons: time availability, teachers' creativity, and competence, materials resources, and class size. The finding strengthens that all elements in the educational system should be ready to run autonomous learning, which involves the readiness of teachers, students, institutions, and the government to support the implementation of autonomous learning in EFL class.